Description of a new Corythucha Stål from Argentina (Hemiptera: Heteroptera: Tingidae), with a description of its life cycle - Montemayor, Sara I. (Zootaxa, 2009)
A new species of the genus Corythucha, C. bonaerensis n. sp., is described along with its egg and all immature stages. It was found in the province of Buenos Aires (Argentina) feeding on Quercus robur, its host plant. Comments on the life history of C. bonaerensis are provided together with photographs, and illustrations. The main differences with the other South American species, and other Corythucha species that feed on Quercus worldwide, are also discussed.